A History of Umbilical Vein Catheterization Does Not Preclude Children from a Successful Meso-Rex Bypass - Lemoine, Caroline P.; Yang, Stephanie; Brandt, Katherine A.; Carra, Sydney; Superina, Riccardo A. (European Journal of Pediatric Surgery, 2023)
Introduction Umbilical vein catheterization (UVC) can cause portal venous thrombosis, leading to the development of extrahepatic portal venous obstruction (EHPVO) and portal hypertension (PHT). The feasibility of the Meso-Rex bypass (MRB) for the treatment of EHPVO in patients with a history of UVC has been questioned. We compared the feasibility of performing an MRB in patients with or without a history of previous UVC.Methods A retrospective review of patients with EHPVO and known UVC status explored for a possible MRB at our institution was performed (1997–2022). Patients were categorized in two groups: with (UVC(+)) or without (UVC(–)) a history of UVC for comparison. A p-value less than 0.05 was considered significant.Results One hundred and eighty-seven patients were included (n = 57 in UVC(+); n = 130 in UVC(–)). Patients in the UVC group were significantly younger at surgery and the incidence of prematurity was higher. Other risk factors for the development of EHPVO were similar between the groups, but only history of UVC could predict the ability to receive MRB (odds ratio [OR]: 7.4 [3.5–15.4]; p < 0.001). The success rate of MRB was significantly higher in patients with no history of UVC (28/57 [49.1%] in UVC(+) vs. 114/130 [87.7%] in UVC(–); p < 0.001). However, MRB patency at discharge (25/28 [89.3%] in UVC(+) vs. 106/114 [94.7%] in UVC(–); p = 0.3) was equally high in both groups.Conclusion Our results indicate that a history of UVC is not a contraindication to MRB. Half of the patients were able to successfully receive an MRB. Patients with symptomatic PHT from EHPVO should not be excluded from consideration for MRB based on UVC history.
Keywords: extrahepatic portal vein obstruction; portal hypertension; Meso-Rex bypass; umbilical vein catheter